2019
DOI: 10.1097/bth.0000000000000259
|View full text |Cite
|
Sign up to set email alerts
|

Radial Head Resection and Corium Interposition Arthroplasty in Skeletally Immature Patients With Isolated Posttraumatic Radial Head Arthrosis

Abstract: Radiocapitellar arthrosis represents a serious sequela of pediatric elbow injuries. Although persistent pain and disability are not uncommon in such cases, treatment remains controversial. The present study aimed to review the clinical outcomes after a new surgical treatment with partial radial head resection and corium interposition arthroplasty. To date, 3 adolescent cases underwent the surgical procedure and postoperative care. Thorough clinical and radiographic follow-up was performed. The mean age at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Some authors have mentioned radial head resection as a salvage procedure for post-traumatic disorders at the proximal radius ( Table 5 ). 4 , 6 , 7 , 10 , 27 , 28 , 32 Weise et al 33 mentioned radial head resection if functional impairment and pain persist after radial head fracture after skeletal maturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have mentioned radial head resection as a salvage procedure for post-traumatic disorders at the proximal radius ( Table 5 ). 4 , 6 , 7 , 10 , 27 , 28 , 32 Weise et al 33 mentioned radial head resection if functional impairment and pain persist after radial head fracture after skeletal maturity.…”
Section: Discussionmentioning
confidence: 99%
“…No proximal migration of the radius had occurred at the final follow-up after 19 months. 32 Factor et al reported four patients (one congenital, three post-traumatic) after radial head excision followed by Achilles allograft interposition arthroplasty with averaged MEPS of 92.5 and improved ROM at 2 years follow-up. In all patients, proximal migration of the radius occurred despite the allograft interposition.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate for the suboptimal fit of the second metatarsal base to the radial notch of the ulna, an additional anconeus interposition ( 49 ), Achilles tendon interposition ( 9 ) or corium interposition ( 11 ) could be options to optimize the radioulnar movability. Alternatively, a costochondral graft has been described especially for bone replacement in children.…”
Section: Discussionmentioning
confidence: 99%
“…The latter may cause a vicious circle of consecutive ulnocarpal impaction syndrome with a need of ulnar shortening procedures due to the proximal radial migration ( 14 ). To prevent such occurrence, multiple interposition arthroplasty techniques have already been described for the pediatric population ( 9 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The surgical approach is similar to the one described previously [ 33 ]. Briefly, a lateral Kocher approach to the elbow patient is performed with the patient lying in the supine position (Fig.…”
Section: Methodsmentioning
confidence: 99%